2013
DOI: 10.1002/prep.201200150
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of PAX‐21 Insensitive Munition Detonation Residues

Abstract: Insensitive high explosives are being used in military munitions to counteract unintended detonations during storage and transportation. These formulations contain compounds such as 2,4‐dinitroanisole (DNAN) and 3‐nitro‐1,2,4‐triazol‐5‐one (NTO), which are less sensitive to shock and heat than conventional explosives. We conducted a series of four tests on snow‐covered ice utilizing 60‐mm mortar cartridges filled with 358 g of PAX‐21, a mixture of RDX, DNAN, and ammonium perchlorate. Rounds were detonated high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…Seven 60-mm rounds filled with PAX-21 explosive (RDX, 2,4dinitroanisole (DNAN), and ammonium perchlorate (AP)) were detonated on the ice and snow covered ERF impact range using the CRREL fuzing system with a 12.6-g C4 booster charge [6]. The detonations did not penetrate the ice cover, and none of the RDAs overlapped with adjacent rounds.…”
Section: Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven 60-mm rounds filled with PAX-21 explosive (RDX, 2,4dinitroanisole (DNAN), and ammonium perchlorate (AP)) were detonated on the ice and snow covered ERF impact range using the CRREL fuzing system with a 12.6-g C4 booster charge [6]. The detonations did not penetrate the ice cover, and none of the RDAs overlapped with adjacent rounds.…”
Section: Testmentioning
confidence: 99%
“…Live-fire testing of munitions from military inventories has been conducted by the US and Canada to quantify energetics residues from combat training. Recently, we have been investigating detonation residues from the new generation of insensitive munitions that have not been certified for firing [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…DR studies are an effective tool to determine the masses of explosive constituents dispersed in representative detonation scenarios. Am ethod for the precise and reliable determination of constituent DR was developed by the Cold Regions and Engineering Laboratory and involves the detonation of munitions items over as urface of pristine snow [8].R DX DRs following the detonation of C4 blocks were tested using this protocol on different occasions and showed that 12 mg to 19 mg of RDX were deposited per C4 block, out of an original mass of 516 go f RDX [9,10].R ecent studies have also been conducted to determine the DR of new insensitive formulations using this method [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…So, much attention in the energetic field is focused on designing new and improved high‐energy materials while insensitive to external stimuli such as impact, friction and electrostatic discharge. A new term “Insensitive Munition (IM)” is proposed, and it represents such munitions, which hardly initiate accidentally and are safe to handle, but still possess enough power and reliability to satisfy the requirements needed in the mission . A large number of researches demonstrate that 1,1‐diamino‐2,2‐dinitroethylene (FOX‐7), 5‐nitro‐1,2,4‐triazole‐3‐one (NTO) and 2,4,6‐triamino‐1,3,5‐trinitro‐benzene (TATB) are known as the current promising candidates of insensitive munitions.…”
Section: Introductionmentioning
confidence: 99%